Morphological and anatomical analyses of the seed coats of sweet granadilla (passiflora ligularis juss.) seeds (2011)
The study of histology and morphology of seeds of genus Passiflora has been of high utility for the classification of species. In seeds of sweet granadilla, the histological characteristics and methodologies for their study are unknown. This study was aimed to know the tissue and morphological characteristics of the seed coats of seeds of sweet granadilla and to be able to determine its value in the differentiation of accessions. Five accessions collected in producing zones of the Province of Huila, Colombia, were analyzed. In morphological analysis, all accessions presented falsifoveate ornamentation and entire margin. The seeds presented high change in weight and size for every accession; there stood out the seeds of the accession PmN for presenting major size (7.42 mm long), weight (35.62 mg), homogeneity in these variables and a typical orange color. For the histological analysis, a protocol was adapted to realize sections of seed coats in parafin, by means of which one managed to obtain sections (7 μ) that in the optical microscope show clearly three well differentiated layers, belonging, possibly, to exotegmen (internal layer), mesotesta (medium layer) and exotesta (external layer). Every layer presented differences in the form of the cells, color and thickness, between the sections of the basal and medium parts of the seeds, but the differences between the analyzed accessions were not observed. The majority of seeds had a thickness of seed coats that varied among 235 and 475 μ.